Foot deformities in children with cerebral palsy. Issue 1 (February 2015) - Kedem, Paz; Scher, David M.
<x xml:space="preserve">Abstract</x> Purpose of review The present article describes common foot deformities in children with cerebral palsy and discusses treatment options for each of those deformities. Recent findings Bracing is a useful treatment to correct foot deformities during gait. Surgical correction of foot deformities is typically performed as a part of multilevel single-event gait improvement surgery that has increasingly become the standard of care for ambulatory children with cerebral palsy. Foot realignment may improve knee function during stance, probably because of change of lever arm. Summary Foot deformities are common among children with cerebral palsy. The three most common among them are equinus, planovalgus and equinovarus/equinocavovarus. Treatment consists of orthotics, physical therapy, spasticity reduction treatment and surgical correction. Guidelines for treatment are individualized and multifactorial. Important considerations include the child's level of function, the severity and flexibility of the deformity, the presence or absence of pain and skin irritation, and the changes in alignment observed over time.